Kinerja Perusahaan Pengaruh dari Struktur Modal, Profitabilitas dan Ukuran Perusahaan - Dede Hertina (El-kahfi | Jurnal Ekonomi Islam, 2020)
This study aims to determine the effect of capital structure, profitability, company size on the performance of the cigarette sub-sector companies listed on the IDX in 2014-2018. This research uses descriptive and verification methods with regression analysis tools and the coefficient of determination. The results of data processing analysis of the coefficient of determination obtained a fairly strong and unidirectional closeness of the relationship between the independent variable and the dependent variable and has a determination coefficient value of 47.91%. The results of testing the F test hypothesis indicate that the capital structure, profitability and company size simultaneously have a significant effect on company performance. Hypothesis testing using t test shows that capital structure has no significant effect on company performance. Profitability has a significant effect on company performance and company size has a significant effect on company performance.